An Examination of Organization Learning and Data Driven Decision Making within Two University Enrollment Management Programs - Martin, Barbara N; Gragg, J. D. (Advances in Social Sciences Research Journal, 2021)
This paper investigated the declining number of students in higher education institutions, and the effective strategies universities can use to recruit students who will graduate. From this research, it appeared that data-driven decision-making can be an effective means to create a successful enrollment management office. Through a practice of data-driven decision-making, organizational learning can happen, which will allow an organization to maintain success and build a culture that sustains that success. Three key themes emerged from the research that will help to inform best practices for other colleges and universities to implement ideas from this research. The three themes are: an organization must have good, usable data; an organization should strive to create a culture of teamwork to sustain success, and an organization needs a successful enrollment leader.